Complete chemistry for Cambridge IGCSE : teacher resource pack - Gallagher, RoseMarie; Ingram, Paul (Oxford : Oxford University Press, 2015)
This new edition of the Teacher's Resource Pack offers expert support for the Cambridge IGCSE Chemistry syllabus. It now includes lesson plans for some of the toughest topics as well as updated classroom support, including worksheets and ideas for practicals. (Source: WorldCat)
Keywords: Chemistry -- Study and teaching (Secondary) -- Great Britain; Chemistry -- Study and teaching (Secondary)